Comparison of Axial Length and Anterior Chamber Depth Measurement among Optical, Applanation and Immersion Biometry (Journal of Shaheed Suhrawardy Medical College, 2019)
Background: Precise biometry is one of the major key factors for obtaining desired refractive outcome after cataract surgery. Visual outcome strongly depends on accuracy of ocular parameters especially axial length (AL) and anterior chamber depth (ACD). It is very important to evaluate different biometry methods to have accurate measurements for IOL power calculation.Objective: The aim of the study is to compare and analyze the difference between the measurement of axial length (AL) and anterior chamber depth (ACD) using ultrasound applanation, immersion and optical biometry.Methodology: A prospective study conducted on 168 patients enrolled for cataract surgery from January 2018 to December 2018 in Dhaka Eye Care Hospital, Dhaka. 280 eyes have been tested by a single observer. Axial length (AL) and anterior chamber depth (ACD) was measured consecutively by optical, applanation and immersion biometry. The results have been statistically evaluated to establish efficacy and correlation among the three methods of biometry.Results: Statistical analysis showed the mean of axial length (AL) obtained from optical biometry is 23.36 ± 1.99 mm, which is 0.10mm (p=0.00) less by applanation biometry and 0.04 mm (p=0.00) less by immersion biometry. For anterior chamber depth (ACD), the mean value from optical biometry is 3.13 ± 0.47mm. This value is highest in compare to both applanation (0.002 mm less with p = 0.824) and immersion (0.04 mm less with p = 0.00) biometry. Further analysis reveals strong correlation of optical biometry with applanation biometry (r = 0.994 for AL and 0.945 for ACD) and immersion biometry (r = 0.995 for AL and 0.947 for ACD).Conclusion: The study reveals that among optical, applanation and immersion method the optical biometry method appeared to be the most precise way of measuring axial length (AL) and anterior chamber depth (ACD) of eye. The study also shows an excellent agreement and strong positive correlation of optical biometry with applanation and immersion biometry.J Shaheed Suhrawardy Med Coll, June 2019, Vol.11(1); 59-64